ECONOMIC SECURITY OF THE ENTERPRISE: MODERN THREATS AND VECTORS OF STRENGTHENING - HRYHORUK, Pavlo; SPIVAK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study revealed the relevance of the issues of managing the economic security of domestic enterprises in the critically complex conditions of today, caused by the systemic negative consequences of a full-scale war. Therefore, the purpose of the study is to identify and generalize the most relevant modern threats and justify the vectors and means of strengthening the economic security of domestic enterprises in the conditions of a full-scale war and the resulting systemic crisis. It is shown that almost all of the systemic challenges and threats to the economic security of business entities, which were characteristic of the domestic business environment at the entire stage of the country's independence, have remained to this day. It is about systemic corruption, administrative pressure on business, tinization and monopolization of economic relations, abuses at customs, which lead to the entry of contraband and gray imports into the domestic market, etc. p. It is argued that these threats were supplemented by new significant challenges for domestic enterprises, which affected the weakening of all components of the economic security of business, especially - financial, intellectual and personnel, production. It is indicated that in the critically difficult situation of the existing market turbulence, enterprises should activate their own security policy and work on strengthening resilience to internal and external challenges, risks and threats. The scientific novelty of the research results lies in the scientific identification of modern challenges and threats to the economic security of economic entities in conditions of full-scale war. The practical significance of the research results lies in the understanding of the challenges, as well as the possibility of approving practical means that allow to guarantee the economic security of domestic enterprises in conditions of systemic crisis and instability.
Keywords: systemic crisis; war; turbulence; instability; challenges and threats; economic security of the enterprise; strengthening of resilience; areas of strengthening; components of security; risk management; security guarantee